2011
DOI: 10.1681/asn.2010111147
|View full text |Cite
|
Sign up to set email alerts
|

Glcci1 Deficiency Leads to Proteinuria

Abstract: Unbiased transcriptome profiling and functional genomics approaches identified glucocorticoid-induced transcript 1 (GLCCI1) as being a transcript highly specific for the glomerulus, but its role in glomerular development and disease is unknown. Here, we report that mouse glomeruli express far greater amounts of Glcci1 protein compared with the rest of the kidney. RT-PCR and Western blotting demonstrated that mouse glomerular Glcci1 is approximately 60 kD and localizes to the cytoplasm of podocytes in mature gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…90 One of the highly glomerulus-specific transcripts identified encodes glucocorticoid-induced transcript 1 (glcci1, ENSMUSG00000029638), which is expressed at 14-fold higher rates in the glomerulus than in the rest of the kidney. 90,91 Glcci1 is highly expressed in mouse glomerular podocytes, and its mRNA and protein levels were upregulated by dexamethasone. 91 The biochemical function of glcci1, including its ligand, is completely unknown.…”
Section: Outlook: Targeting Energy Metabolism In Podocytes As a Futurmentioning
confidence: 99%
See 1 more Smart Citation
“…90 One of the highly glomerulus-specific transcripts identified encodes glucocorticoid-induced transcript 1 (glcci1, ENSMUSG00000029638), which is expressed at 14-fold higher rates in the glomerulus than in the rest of the kidney. 90,91 Glcci1 is highly expressed in mouse glomerular podocytes, and its mRNA and protein levels were upregulated by dexamethasone. 91 The biochemical function of glcci1, including its ligand, is completely unknown.…”
Section: Outlook: Targeting Energy Metabolism In Podocytes As a Futurmentioning
confidence: 99%
“…90,91 Glcci1 is highly expressed in mouse glomerular podocytes, and its mRNA and protein levels were upregulated by dexamethasone. 91 The biochemical function of glcci1, including its ligand, is completely unknown. However, based on its amino acid sequence, which shows > 60 serine/ threonine phosphorylation sites in the approximately 60-kDa protein, glcci1 may be a powerful substrate for a large number of signaling kinases and may thereby interfere with their activation by depriving them of energy.…”
Section: Outlook: Targeting Energy Metabolism In Podocytes As a Futurmentioning
confidence: 99%
“…17 Therefore, several investigators have successfully used the fish model system to show that deletion of genes in podocytes resulted in podocyte dysfunction and deficiency of the size-selective kidney barrier. [17][18][19][20][21][22][23][24] Over the past several years, zebrafish have emerged as an ideal model to study vertebrate development. The transparency of the zebrafish embryos allows direct visualization of tissue morphogenesis such as glomerular development as it occurs in a live organism.…”
mentioning
confidence: 99%
“…These assays seem to be both fairly costintensive, especially when considering large-scale screens, and largely dependent on assay techniques. 23 Using a fluorescent marker of proteinuria overcomes most of these limitations, which may be interesting in the future. From the perspective of a nephrologist, screening for novel drugs that prevent podocyte death and the development of progressive glomerulosclerosis would be most desirable.…”
mentioning
confidence: 99%
“…In the current issue of JASN, Nishibori et al report on another one of the more than 300 genes originally identified by this group. 7 Glucocorticoid-induced transcript 1, GLCCI1, is expressed in the glomerulus of the mouse kidney at an elevated level, according to their GlomBase and GlomChip data. 8 In the current article, this group confirms the original data, first with an in vitro analysis, followed by immunohistochemistry.…”
mentioning
confidence: 99%